Ответы и объяснения

Лучший Ответ!
  • IOriOnI
  • почетный грамотей
2012-05-22T19:05:14+04:00

2(sin2x+1)(2sinx- корень из 3)=0

(sin2x+1)=0  -> sin2x=-1  ->2x= -pi/2+2pi*k  ->x= -pi/4+pi*k

2sinx- 3=0  ->sinx=3/2  -> x=(-1)^n  *pi/3 + pi*n

2012-05-22T19:08:20+04:00

2(sin2x+1)(2sinx- корень из 3)=0

sin2x + 1 = 0 или 2sinx - корень из 3 = 0

sin2x= -1 или sinx = корень из 3/2

2x = -пи/2 + 2пиk    или x = (-1)степень k * пи/3 + пиk

x= - пи/4 + пиk, где k принадл. Z или x = (-1)степень k * пи/3 + пиk, где k принадл. Z